Human rights and humanitarian law - South Asia Human Rights Documentation Centre (New Delhi, 2008)
This book is designed as a basic text for MA and LLM students at Indian Universities pursuing courses in human rights and related courses, including criminology and legal administration. It give a comprehensive idea of jurisprudential issues, all relevant international conventions, Indian constitutions and statutory provision, as well as case law.
Keywords: Human rights